Culture in the Borderlands: "Stories" of Southeast Asian Domestic Workers in Taiwan - Sheu, Huey-jen (2008)
Migration and mobility is not a new phenomenon in human society. Historically, people have moved from one place to another either for reasons of survival or due to force in terms of slavery. Compared to the past centuries, migration in recent years has increased in dimension for both the sending and the receiving communities. The increase in economic disparities, the internationalization of the market and increasing numbers of individuals seeking employment outside their own countries, and demographic developments all promote this trend. In Taiwan, migrant women are the primary source of paid domestic labor. Taiwan is becoming a land of dreams and also a land of tears for these migrant women. I interviewed and spent time with dozens of Southeast Asian domestics working in and around Taipei as well as some of their Taiwanese employers. On the basis of these data I collected, I Interweave my analysis with the women's individual stories, and also demonstrate how economic factors, immigration policies, the intermediaries, ethnicity, and gender intersect in the relationship between migrant women and the Taiwanese people.
Erscheinungsjahr an der Haupttitelstelle: 2007
Keywords: Hochschulschrift; Migration; Arbeiter; Taiwan; Südostasien